STUDENTS' PERCEPTION OF PERFOMANCE-BASED ASSESSMENT APPLICATION IN HIGHER EDUCATION - Amalul - Umam; Fidini Peparing Mauludi; Muhammad Kiki Wardana (Universitas Majalengka, 2021)
Learning process needs to be well-planned by the teachers in 21st century. It aims to build the students’ character to be more professional facing social-life problem. To evaluate, Performance-Based Assessment (PBA) has been implemented by many states which emphasizes the performance-skills of demonstrating ideas such as presentations, debate, making papers, shows etc. Its function of engaging students’ interest in subject and as teachers’ way of assessing students’ capability. For college students, doing group presentation has been done in many times and mostly implemented as assignments. However, students’ opinions toward this assessment must be important case for teachers’ evaluation. This paper is made to find out and analyze students’ perception on PBA in university level.